Lung Transplantation From Controlled and Uncontrolled Donation After Circulatory Death (DCD) Donors With Long Ischemic Times Managed by Simple Normothermic Ventilation and Ex-Vivo Lung Perfusion Assessment - Palleschi, Alessandro; Zanella, Alberto; Citerio, Giuseppe; Musso, Valeria; Rosso, Lorenzo; Tosi, Davide; Fumagalli, Jacopo; Bonitta, Gianluca; Benazzi, Elena; Lopez, Gianluca; Rossetti, Valeria; Morlacchi, Letizia Corinna; et al. (Transplant international, 2023)
Donation after cardiac death (DCD) donors are still subject of studies. In this prospective cohort trial, we compared outcomes after lung transplantation (LT) of subjects receiving lungs from DCD donors with those of subjects receiving lungs from donation after brain death (DBD) donors (ClinicalTrial.gov: NCT02061462). Lungs from DCD donors were preserved in-vivo through normothermic ventilation, as per our protocol. We enrolled candidates for bilateral LT ≥14 years. Candidates for multi-organ or re-LT, donors aged ≥65 years, DCD category I or IV donors were excluded. We recorded clinical data on donors and recipients. Primary endpoint was 30-day mortality. Secondary endpoints were: duration of mechanical ventilation (MV), intensive care unit (ICU) length of stay, severe primary graft dysfunction (PGD3) and chronic lung allograft dysfunction (CLAD). 121 patients (110 DBD Group, 11 DCD Group) were enrolled. 30-day mortality and CLAD prevalence were nil in the DCD Group. DCD Group patients required longer MV (DCD Group: 2 days, DBD Group: 1 day, p = 0.011). ICU length of stay and PGD3 rate were higher in DCD Group but did not significantly differ. LT with DCD grafts procured with our protocols appears safe, despite prolonged ischemia times.